The cost minimization analysis of an outreach dental service: a pilot study at akinyele local government area in Nigeria (2016)
Access to dental services improves oral health and thereby, overall general health. For people with limited or no access to oral health care services, outreach dental services may be used to reduce oral health inequality. There is however paucity of information on the economic analysis of outreach dental services in sub Saharan Africa. To report a cost minimization analysis of an outreach dental service as compared with a primary oral health clinic. A comparative analysis of the costs expended in the treatment of patients at an outreach dental service of the University College Hospital, Ibadan was done versus the costs that would have been incurred if the patients had been treated at a Primary Oral Health Clinic of the same institution. A total of three hundred and forty two (342) participants were attended to at the outreach dental service. More than 80% of the 123 participants examined had an unmet oral health need. The procedures carried out were in keeping with the basic package of oral care. The average cost of the outreach per participant was N530 (~$2.50) only versus an estimate of N868 (~$4.13) per participant if the programme had been clinic based. The total cost savings was N115,344 (~$549.26). Outreach dental services provide similar dental treatment to services in a primary oral health clinic at a reduced cost